2013
DOI: 10.1002/ajmg.a.36331
|View full text |Cite
|
Sign up to set email alerts
|

Dysspondyloenchondromatosis without COL2A1 mutation: Possible genetic heterogeneity

Abstract: Dysspondyloenchondromatosis is a rare form of generalized enchondromatosis associated with spinal involvement. This skeletal dysplasia is characterized by multiple enchondromas present in vertebrae as well as in metaphyseal and diaphyseal parts of the long tubular bones, post-natal short stature, and early development of kyphoscoliosis. A novel heterozygous missense mutation in COL2A1 was recently identified in a patient with dysspondyloenchondromatosis. This suggests that dysspondyloenchondromatosis might exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Dysspondyloenchondromatosis is inherited as an autosomal dominant trait caused by heterozygous mutations in COL2A1 . This syndrome is characterized by short stature with unequal limb length, multiple metaphyseal and diaphyseal enchondromas in the long tubular bones, and osteopenia . Spondyloenchondrodysplasia is an immuno‐osseous dysplasia caused by biallelic mutations in ACP5 …”
Section: Multiple Enchondromas (Aka Enchondromatosis)mentioning
confidence: 99%
“…Dysspondyloenchondromatosis is inherited as an autosomal dominant trait caused by heterozygous mutations in COL2A1 . This syndrome is characterized by short stature with unequal limb length, multiple metaphyseal and diaphyseal enchondromas in the long tubular bones, and osteopenia . Spondyloenchondrodysplasia is an immuno‐osseous dysplasia caused by biallelic mutations in ACP5 …”
Section: Multiple Enchondromas (Aka Enchondromatosis)mentioning
confidence: 99%
“…They noted that the chondromatous changes in DSC are expected to be regressive rather than progressive. We compared the clinical and radiological features of the patients in this study to those previously reported 15 patients with DSC in Table 1 [Mainzer et al, 1971;Spranger et al, 1978;Azouz, 1987;Lerman-Sagie et al, 1987;Freisinger et al, 1993;Kozlowski et al, 1994;Nakane et al, 2011;Kenis et al, 2013;Tran Mau-Them et al, 2014;Merrick et al, 2015]. All patients except for the patient of Tran MauThem et al [2014] had asymmetric limb shortening.…”
Section: Discussionmentioning
confidence: 92%
“…However, a further case of DSC without unequal limbs was reported in which no pathogenic mutation was identified, suggesting that DSC is genetically heterogeneous [Tran Mau-Them et al, 2014]. Recently, Merrick et al [2015] also reported a mutation in COL2A1 in a patient with DSC.…”
mentioning
confidence: 99%
“…They demonstrated a novel mutation (p.Gly753Asp) in the COL2A1 gene in a patient with DSC, indicating that the condition is part of the broad spectrum of type II collagen disorders [Nakane et al, ]. However, a further case of DSC was subsequently reported in which no pathogenic mutation was identified, suggesting that the condition is genetically heterogeneous [Tran Mau‐Them et al, ].…”
Section: Introductionmentioning
confidence: 99%